OP0026 Synovial Fluid Mononuclear Cells Provide An Environment for Long-Term Survival of Antibody Secreting Cells and Promote The Spontaneous Production of Anti-Citrullinated Protein Antibodies. (15th July 2016) - Kerkman, P.F.; Kempers, A.C.; van der Voort, E.I.; van Oosterhout, M.; Huizinga, T.W.; Toes, R.E.; Scherer, H.U.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by the presence of antibodies against citrullinated protein antigens (ACPA). The striking efficacy of B cell-depleting interventions and an increasing number of experimental observations suggest that ACPA and/or ACPA-expressing B cells could be actively involved in initiating, aggravating and/or perpetuating the disease process. We recently demonstrated that ACPA-expressing B cells circulate in the peripheral blood of patients with ACPA-positive RA 1, 2 . Next to ACPA-expressing memory B cells, we could identify a population of plasmablasts/-cells (PB/PC) that actively secrete ACPA in this compartment. To date, however, it is unknown whether these circulating PB/PC home to secondary lymphoid organs to compete for survival niches, or whether the synovial compartment of inflamed joints could be one of the tissues attracting these cells. As PC can produce excessive amounts of antibodies and survive in respective niches for years, they could be involved in driving and maintaining disease-specific pathogenic processes. Objectives: To study whether cells from the synovial environment impact on the longevity of auto-reactive B cell responses against citrullinated antigens. Methods: Synovial fluid and peripheral blood mononuclear cells (SFMC/PBMC) were obtained from patients with established RA and assessed for the presence of B cell subpopulations. Cells spontaneously secreting ACPA-IgG directly ex vivo were detected and enumerated by antigen-specific ELISpot. In addition, SFMC and PBMC were cultured without additional stimuli to assess the degree of spontaneous ACPA-IgG secretion. Cells surviving for several weeks in culture were characterized by CFSE-labelling and Ki-67 staining. Results: Cells spontaneously secreting ACPA-IgG were readily detectable in peripheral blood and synovial fluid (SF) of ACPA-positive RA patients. SFMC showed an up to 200-fold increase in ex vivo ACPA-IgG secretion compared to PBMC despite lower numbers of B cells in SFMC. ELISpot confirmed the presence of spontaneously ACPA-IgG secreting cells, accounting for up to 50% (median 12%) of all IgG-secreting cells in SF. Spontaneous ACPA-IgG secretion was remarkably stable in SFMC cultures, maintained upon depletion of the CD20 + B cell compartment prior to culture, and detectable for several months. CFSE labelling and Ki-67 staining confirmed the long-term survival of non-dividing plasma cells. Conclusions: This study demonstrates a high frequency of differentiated, spontaneously ACPA-IgG secreting cells in SF. These cells are supported by SFMC for prolonged survival and autoantibody secretion, demonstrating that the synovial compartment is equipped to function as inflammatory niche for plasma cell survival. References: Kerkman PF et al. Ann Rheum Dis. 2013 Jul;72(7):1259–63. Kerkman PF et al. Ann Rheum Dis. 2015 Jun 1. doi: 10.1136/annrheumdis-2014-207182. Acknowledgement: Supported by grants from the Dutch Arthritis Foundation, The Netherlands Organization for Scientific Research and the Innovative Medicines Initiative funded project BeTheCure. Disclosure of Interest: None declared